Evaluasi Pelaksanaan Ujian Online Dengan E-Learning Universitas Negeri Padang - Eliza, Fivia; Ambiyar, Ambiyar (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2024)
Learning using E-Learning has recently become part of education in Indonesia, however its implementation needs to be evaluated so that it meets standards. So, this research aims to start implementing Online exams using Padang State University E-Learning. This research is evaluation research using the Context, Input, Process, Product (CIPP) approach. The research subjects were 30 students taking measurement and instrument lectures in the electrical engineering study program, Faculty of Engineering, Padang State University. The instrument used in this research was a questionnaire. The data was analyzed for the average value of the questionnaire which was classified and explained for each aspect of the evaluation. The research results that describe the implementation of Online exams with E-Learning at Padang State University are quite good, with average scores reflecting adequate quality. Context evaluation indicates the user's skill level and sufficient means available, although graphics and E-Learning content require further attention. Evaluation input shows good improvements in user capabilities and availability of E-Learning access facilities. The evaluation highlights the good process of using E-Learning applications, despite challenges in implementing assessments through the platform. Product evaluation shows that the quality and benefits of E-Learning are quite good. In conclusion, although the implementation of Online exams has provided positive benefits, there are still aspects that can be improved, such as the security of Online exams and more authentic evaluation methods. These findings provide valuable insight for further development in facing the dynamics of educational technology that continues to develop. The findings of this research open up opportunities for further exploration in the use of Artificial Intelligence (AI) in conducting Online exams.